Arbitration and the Emergence of Sectarianism: A Historical Examination of the Transition of Conflict from Politics to Theology - Deni Irawan; Kasman Kasman; Safrudin Edi Wibowo; Miftah Arifin (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
The schism within the Islamic community reached its zenith following the Battle of Ṣiffīn, when the process of Taḥkīm, intended to alleviate the conflict between Ali ibn Abi Talib and Muawiyah ibn Abi Sufyan, instead incited theological divisions. This research focuses on how Taḥkīm transformed the dispute from practical politics into doctrinal debate, giving rise to various sectarian movements. This study aims to critically and historically examine the role of Taḥkīm in the emergence of sects such as the Khawārij, Shīʿah, Murjiʾah, and other theological factions. The methodology employed is a literature review, analysing classical documents and contemporary academic literature that discuss the socio-political context, the arbitration process, and the responses of various groups following Taḥkīm. The findings indicate that this arbitration not only resolved military disputes but also served as a catalyst for the formation of a fragmented Islamic intellectual structure. The implications of this study underscore the importance of re-reading the history of internal Islamic conflict in an objective and inclusive manner, enabling the community to learn from past experiences, maintain unity, and avoid the politicisation of religion that could undermine brotherhood.